Innovation Patterns and Their Effects on Firm-Level Productivity in South Asia - Cirera, Xavier; Cusolito, Ana P. (World Bank, Washington, DC, 2019)
This paper describes and benchmarks innovation activities for a sample of countries in the South Asia region, as well as the impact of these activities on firm-level productivity. The evidence gathered suggests that countries in the South Asia region can be divided into two groups, in terms of the magnitude and composition of the innovation activities: leaders (Bangladesh and India) and laggards (Nepal and Pakistan). Leaders present higher rates of innovation activities than laggards and focus more on process innovation than product innovation. Differences across firms within all countries tend to present similar patterns when considering leaders and laggards, with the acquisition of knowledge capital (for example, research and development investments in equipment, and training) highly concentrated in a few firms, and mature, exporter, and foreign-owned firms as the most innovative of the region. The evidence also suggests a positive impact of innovation on productivity, primarily via incremental innovation, especially in India.